The influence of customer complaint management on brand image in building customer loyalty in telecommunication sector - Achilova, Zarrina (My University, 2019)
In this research, we investigate the influence of customer complaint management on the brand image in building customer loyalty. The object of this research is to investigate how managing the processing of subscriber’s complaints in Tajikistan Mobile Company Tcell can influence subscriber’s perception of the brand image and the level of loyalty. In this study, both secondary and primary data were used. Secondary data were obtained from the kinds of literature and Business Intelligence Department of Tcell and a questionnaire was used as the primary source of data collection. The respondents were only Tcell subscribers, who previously had experience of applying complaints with company. The result of this study is that handling complaints has a moderate influence on brand image and customer loyalty. The level of loyalty is more influenced by the brand image. The study also showed that the process and channels for applying and processing complaints in Tcell are well established, but subscribers are not satisfied with the issue of compensation for company failures. Subscribers believe that Tcell does not pay much attention to company falures compensation to subscribers and thus does not satisfy them.

In this research, we investigate the influence of customer complaint management on the brand image in building customer loyalty. The object of this research is to investigate how managing the processing of subscriber’s complaints in Tajikistan Mobile Company Tcell can influence subscriber’s perception of the brand image and the level of loyalty. In this study, both secondary and primary data were used. Secondary data were obtained from the kinds of literature and Business Intelligence Department of Tcell and a questionnaire was used as the primary source of data collection. The respondents were only Tcell subscribers, who previously had experience of applying complaints with company. The result of this study is that handling complaints has a moderate influence on brand image and customer loyalty. The level of loyalty is more influenced by the brand image. The study also showed that the process and channels for applying and processing complaints in Tcell are well established, but subscribers are not satisfied with the issue of compensation for company failures. Subscribers believe that Tcell does not pay much attention to company falures compensation to subscribers and thus does not satisfy them.
Keywords: Brand Image; Brand name products; Branding; Consumer behavior; Customer Churn; Customer Journey; Customer loyalty; Marka İmajı; Markalaşma; Markalı ürünler; Marketing; Müşteri sadakati; Pazarlama; Şikayet Yöntemi Customer Complaint Management; Tüketici davranışı